Status of Radiation Protection Measures in Private Medical Facilities in Pirojpur District of Bangladesh - Ahmed, E.; Hossain, M. T.; Sarker, B. K.; Hossain, F.; Ahmed, S.; Karmkar, R. C.; Akramuzzaman, M. (Journal of Scientific Research, 2026)
Radiation safety is a key concern to protect workers, patients, and the public from ionizing radiation. This study investigates the status of radiation protection in 35 private medical facilities in Pirojpur district through field inspections, structured interviews, and radiation dose measurements, in accordance with national safety standards (BAER Act-2012, NSRC Rules-1997, and Regulatory Guides). The results show that 60 % of facilities lack a certified RCO, and 34 % of facility operators do not use a personal monitoring device, violating Sections 54.0, 58.1, and 59.1 of the NSRC Rules-1997. While most of the X-ray rooms are undersized, 86 % meet wall thickness requirements (Regulatory Guide for Diagnostic X-ray). 80 % of facilities have radiation warning signs and 88.5 % of facilities use PPE, which are safety requirements according to Sections 55.2 (a), 18.2 (22), and 83.1 (b) of NSRC Rules-1997. Radiation doses at control panels were within the limit in most cases, but the doses at the entrance doors were not satisfactory. The use of shielding materials was sufficient in most facilities. Compared with the previous regulatory survey, notable progress has been observed. However, to foster safe and effective radiological practice, awareness needs to increase by providing proper guidance, training, and regulatory support.